Online and Kicking: Sign Language Activism via Social Media - Leeson, Lorraine (My University, 2019)
Online activism in the Irish Deaf community demonstrates leveraging of multimodal linguistic repertories (as per Kusters et al 2017) ; it started as community-led work towards ISL recognition. Some fora are more ISL-led, community facing (FaceBook) while others are more outward facing, and in English (Twitter). Twitter has facilitated connectivity with other activists working from linguistic, political or issue-specific work. It has also facilitated increased mainstream media attention. Success with the ISL campaign has bred subsequent successes, and supported young leaders in their drive to engage on subjects that are not ‘Deaf community specific”, e.g. “Deaf Community for Yes”. Subsequent to this, we see deaf people in Ireland engaging in mainstream politics for the first time.
ICMLXVII Colloquium Virtual communities a breathing space for minority languages
Keywords: Identities in Transformation; Inclusive Society; Irish Sign Language; Irish Sign Language Act 2017; REPEAL; TogetherForYes; WheresTheAccess; YestoISL; Deaf/Deafness; Gender; Social exclusion; Social participation